Human Development: Means and Ends (The Quaid-i-Azam Lecture) (The Pakistan Development Review, 1995)
Sometimes the change in the fashions of thinking about development appears like a comedy of errors, a lurching from one fad to another. Economic growth, employment creation, jobs and justice, redistribution with growth, basic needs, bottom-up development, participatory development, sustainable development, market-friendly development, liberation, liberalisation, human development; thus goes the carousel of the slogans. But this would not be a correct record. There has been an evolution in our thinking about development. Both internal logic and new evidence have led to the revision of our views. Previous and partly discarded approaches have taught us much that is still valuable, and our current approach will surely be subject to criticisms. A brief survey of the evolution of our thinking may be helpful. The discussion started in the 1950s, influenced by Arthur Lewis (1955) and others, who emphasised economic growth as the key to poverty eradication. Even at this early stage, sensible economists and development planners were quite clear (in spite of what is now often said in caricature of past thought) that economic growth is not an end in itself, but a performance test of development. Arthur Lewis defined the purpose of development as widening our range of choice, exactly as the Human Development Reports of the United Nations Development Programme do today.